Relationship Between Creativity With Self-Concept of Student Junior High School 2 Padang - Atikah Suri Jania; Netrawati Netrawati (Jurnal Neo Konseling, 2019)
Adolescence is a transition from childhood to adulthood. In this case the change in social interaction and self-control is influenced by one's self-concept. By having a positive self-concept students are able to accept their condition and maximize their potential. However, in reality there are still students in the field who have a negative self-concept that feels themselves are insignificant, are very sensitive to criticism and feel pessimistic every time they encounter a problem. The concept of self is an individual's perception of himself, his abilities, and one of the determinants of someone in being good or bad so that it can cause changes in knowledge, attitudes, behavior and it is suspected that one of the factors that influence it is creativity. This study aims to determine the relationship between creativity and self-concept of students of Junior High Shcool 2 Padang. This research is a descriptive correlational research with quantitative methods. A total of 223 students were selected using the Simple Random Sampling technique. The research instrument used was a questionnaire of creativity and student self-concept questionnaire with a Likert scale model. The results revealed that (1) the creativity of students in Junior High School 2 Padang as a whole was categorized as high (2) the self-concept of students in Junior High School Padang as a whole was categorized as high (3) there was a significant relationship between creativity and the students' self concept in Junior High School 2 Padang. Based on the research findings, it is recommended that school counselors/school counselors be able to provide guidance and counseling services, namely information services and individual counseling services in order to help students who have problems with self-concept.